2022
DOI: 10.7241/ourd.20221.7
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dermatophytosis: A clinical, epidemiological, mycological study

Abstract: Background: Dermatophytes are a common cause of superficial fungal infection of the skin. The emergence of epidemic-like attacks of those chronic and recurring represents a public health problem. Materials and Methods: Two hundred patients with suspected fungal infection of the skin attending the Dermatology and Venereology Department of Al-Ramadi Teaching Hospital were examined. Fifty-nine patients with chronic dermatophytosis were selected for the study and fifty of those were subjected for culture. History… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The clinical form of this fungus in our patient indicated a good therapeutic response to Penicillin G. However, previous studies have demonstrated positive antifungal activity with azoles and amphotericin B treatment for Trichosporon infection [5]. Other forms of treatment, such as the resection of the infected tissue, are associated with greater improvement [5,6].…”
Section: Case Lettermentioning
confidence: 53%
“…The clinical form of this fungus in our patient indicated a good therapeutic response to Penicillin G. However, previous studies have demonstrated positive antifungal activity with azoles and amphotericin B treatment for Trichosporon infection [5]. Other forms of treatment, such as the resection of the infected tissue, are associated with greater improvement [5,6].…”
Section: Case Lettermentioning
confidence: 53%
“…Nevertheless, both time kills occurred after 6 and 24 h, respectively (Figure S7). These differences in inhibition times could be explained because the isolates have different origins and individual biological aspects (incorrect drug dosage and immunological problems) . The cell’s viability began to deteriorate with each passing day of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus propagates in about 20 minutes [13], whereas clostridium spp. even in 10 minutes [14]. Among the microorganisms inhabiting human skin, there are also anthropophilic fungi that develop within a few days.…”
Section: Impact Of Masks On Facial Skin Conditionmentioning
confidence: 99%